Perennials for the Pacific Northwest : 500 best plants for flower gardens - Wingate, Marty (Sasquatch Books, 2013)
"Perennials--plants that grow for at least three years--are the best choice for gardeners who want a year-round succession of flowers, form, and foilage. With this up-to-date selection of plants that are perfect for Pacific Northwest gardens, you can achieve beauty, fragrance, and success in the garden"--Provided by publisher.